Innate immune responses in Behçet disease and relapsing polychondritis - Shimizu, Jun; Murayama, Masanori A.; Mizukami, Yoshihisa; Arimitsu, Nagisa; Takai, Kenji; Miyabe, Yoshishige (Frontiers in Medicine, 2023)
Behçet disease (BD) and relapsing polychondritis (RP) are chronic multisystem disorders characterized by recurrent flare-ups of tissue inflammation. Major clinical manifestations of BD are oral aphthae, genital aphthous ulcers, skin lesions, arthritis, and uveitis. Patients with BD may develop rare but serious neural, intestinal, and vascular complications, with high relapse rates. Meanwhile, RP is characterized by the inflammation of the cartilaginous tissues of the ears, nose, peripheral joints, and tracheobronchial tree. Additionally, it affects the proteoglycan-rich structures in the eyes, inner ear, heart, blood vessels, and kidneys. The mouth and genital ulcers with inflamed cartilage (MAGIC) syndrome is a common characteristic of BD and RP. The immunopathology of these two diseases may be closely related. It is established that the genetic predisposition to BD is related to the human leukocyte antigen (HLA)-B51 gene. Skin histopathology demonstrates the overactivation of innate immunity, such as neutrophilic dermatitis/panniculitis, in patients with BD. Monocytes and neutrophils frequently infiltrate cartilaginous tissues of patients with RP. Somatic mutations in UBA1, which encodes a ubiquitylation-related enzyme, cause vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic syndrome (VEXAS) with severe systemic inflammation and activation of myeloid cells. VEXAS prompts auricular and/or nasal chondritis, with neutrophilic infiltration around the cartilage in 52-60% of patients. Thus, innate immune cells may play an important role in the initiation of inflammatory processes underlying both diseases. This review summarizes the recent advances in our understanding of the innate cell-mediated immunopathology of BD and RP, with a focus on the common and distinct features of these mechanisms.